The Turkish Arms Embargo : Drugs, Ethnic Lobbies, and US Domestic Politics. - Goode, James F. (Lexington : University Press of Kentucky, 2020)
"American ties to the Republic of Turkey and earlier to the Ottoman Empire have a long and sometimes tumultuous history. After World War II, as the United States and the Soviet Union drifted apart, the Truman administration did what it could to strengthen ties with Turkey. The greatest threat to harmonious relations between the two nations began in the early 1960s, shortly after the establishment of an independent Cyprus. A few years later, strained relations between Greek and Turkish communities on Cyprus reached a tipping point, and in his infamous "Johnson Letter," President Johnson denied Turkey American weapons for military intervention and warned that NATO might not be obliged to come to Turkey's defense. Although an invasion and war did not happen then, the Johnson Letter alienated both the Greek and the Turkish governments. In 1974 the Cypriot National Guard and the Greek military junta backed the Cypriot coup d'etat, and Turkey sent its forces to Cyprus under the guise of protecting the safety of Turkish Cypriots. Instead, Turkey took control of the northern third of Cyprus and divided the island along what became known as the Green Line, which is monitored to this day by the United Nations. In response to the coup, the US Congress imposed an embargo on arms sales to Turkey that led to further tension and mistrust between the two countries. In Drugs, Ethnic Lobbies, and Domestic Politics: Understanding the Crisis in US-Turkish Relations, 1974-1978, author James Goode focuses on the complex factors leading to the imposition of the Turkish Arms Embargo following the invasion of Cyprus and the impact on relations between the two NATO allies as the embargo continued through two administrations. The manuscript, rooted in US domestic politics, offers new insights regarding the struggle between President Ford and Congress to bring about their respective desired results in policy, as well as Carter administration policy that facilitated the end of the embargo in 1978. Goode also provides a new understanding of the pervasive influence of both the drug crisis and Turkophobia in prolonging the confrontation."--
Front Cover -- Title Page -- Copyright Page -- Dedication -- Contents -- Illustrations -- Abbreviations -- Preface -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Conclusion -- Epilogue -- Acknowledgments -- Appendix -- Notes -- Bibliography -- Index -- Seires Page.
Print version record.
JSTOR
Keywords: United States -- Politics and government -- 1974-1977.; Cyprus -- History -- Turkish Invasion, 1974.; Turkey -- Foreign relations -- United States; United States -- Foreign relations -- Turkey; Turkey -- Military relations -- United States; United States -- Military relations -- Turkey; Greek Americans -- Political activity -- 20th century; Drug traffic -- Turkey; Military assistance, American -- Turkey; États-Unis -- Politique et gouvernement -- 1974-1977.; Chypre -- Histoire -- 1974 (Invasion turque); Asie Mineure -- Relations militaires -- États-Unis.; Américains d'origine grecque -- Activité politique -- 20e siècle.; HISTORY -- United States -- 20th Century; POLITICAL SCIENCE -- International Relations -- Diplomacy; Diplomatic relations; Drug traffic; Greek Americans -- Political activity; Military assistance, American; Military relations; Politics and government; Cyprus; Turkey; United States; 1900-1999; History